Pengaruh Variasi Konsentrasi NaOH Terhadap Nilai Derajat Deasetilasi Kitosan dari Limbah Cangkang Kerang Hijau (Perna viridis L): The Effect of NaOH Concentration on The Value of The Deacetylation Degree of Chitosan from Green Mussels Shell Waste (Perna viridis L) - Nurzaman; Winda Trisna Wulandari; Anindita Tri Kusuma Pratita; Keni Idacahyati (KOVALEN: Jurnal Riset Kimia, 2020)
Chitin which is the result of processing from green conch shell waste can be transformed into chitosan through a deacetylation process using variations in the concentration of NaOH. This study aims to determine the optimum conditions of variations in base concentration to the value of the degree of deacetylation of chitosan. The types of bases used are NaOH with the concentration variations of 50%, 55%, and 60%. Chitosan obtained was calculated the yield and characterized using FTIR. The results showed the optimum condition of the value of chitosan deacetylation degree was achieved by using 60% NaOH which produced the highest deacetylation degree value of 76.5%. Keywords: Green mussels shell, chitin, chitosan, deacetylation